Implementation of batchwise bioscouring of cotton knits - Choe, Eun Kyung (2004)
The examination of critical factors determining the performance of bioscouring showed that a short treatment of the fabric at greater than 80°C after pectinase treatment at 60°C was essential for removal of waxes from the fabric as demonstrated by diminished intensities of methylene peaks in FT-IR measurements. Batch-wise bioscouring of cotton knits was carried out several times with post-treatment at 80°C using a rapid dyeing machine. The dye-ability of bioscoured knits was as good as the company's alkaline scoured ones with slightly higher K/S values. Water pollution caused by effluents of bioscouring and alkaline processes were estimated, as well as that due to the input of chemicals and enzymes. Higher BOD:CODCr ratios for enzymes indicated their biodegradable character. After calculation of energy consumption using a simulation program, an economic evaluation of the two processes was done on the basis of one ton production by considering the costs of chemicals and enzyme, water usage, energy consumption and waste water treatment charge.